Analysis of the Effect of Core Thickness and Rotational Speed on the 24 Slot 16 Pole Permanent Magnet Synchronous Generator on PMSG Characteristics - Syarief, Ahmad Ridwan; Liliana, Liliana (Program Studi Teknik Elektro Universitas Khairun, 2024)
Electrical energy has become a basic need that cannot be eliminated in everyday life for Indonesian people, where the source of electrical energy is currently still fossil fuels. One way to overcome excessive exploitation of fossil fuels is to utilize renewable energy sources, namely wind energy. Wind has a great potential for generating electrical energy with the conversion that occurs in the Permanent Magnet Synchronous Generator (PMSG). PMSG is one of the components in a wind power plant (PLTB). Current wind conditions in Indonesia cause low efficiency in PMSG, where many things affect this, one of which is power losses in the generator, copper losses caused by the copper winding on the stator getting hot, and iron losses because the generator has bearings. get hot. Many factors can cause efficiency to increase, such as the core speed and core thickness used in PMSG. In this paper, an image of the 24 slot, 16 pole PMSG model will be created with variations in rotational speed and core thickness using the MagNet Infolytica software by simulating the software using the Finite Element Method (FEM). Variations of speed used are 250 rpm, 500 rpm, and 750 rpm, with variations in core thickness of 40 mm, 60 mm, and 80 mm. The simulation results that occur in variations in current, voltage, torque, input power, and input power all increase according to Faraday's law. The highest efficiency value was obtained at 82.20% at a core thickness of 40 mm and a rotating speed of 500 rpm, with a current value of 9,926 Amperes, a voltage of 99,263 Volts, a torque of -22,904 Nm, an input power of 1198.64 Watts, and an output power of 985.28 Watts